Screening for predictors of adverse outcome in onco-geriatric surgical patients: A multicenter prospective cohort study. Issue 7 (July 2015) - Huisman, M.G.; Audisio, R.A.; Ugolini, G.; Montroni, I.; Vigano, A.; Spiliotis, J.; Stabilini, C.; de Liguori Carino, N.; Farinella, E.; Stanojevic, G.; Veering, B.T.; Reed, M.W.; et al.
Abstract Aims The aim of this study was to investigate the predictive ability of screening tools regarding the occurrence of major postoperative complications in onco-geriatric surgical patients and to propose a scoring system. Methods 328 patients ≥70 years undergoing surgery for solid tumors were prospectively recruited. Preoperatively, twelve screening tools were administered. Primary endpoint was the incidence of major complications within 30 days. Odds ratios (OR) and 95% confidence intervals (95% CI) were estimated using logistic regression. A scoring system was derived from multivariate logistic regression analysis. The area under the receiver operating characteristic curve (AUC) was applied to evaluate model performance. Results At a median age of 76 years, 61 patients (18.6%) experienced major complications. In multivariate analysis, Timed Up and Go (TUG), ASA-classification and Nutritional Risk Screening (NRS) were predictors of major complications (TUG>20 OR 3.1, 95% CI 1.1–8.6; ASA≥3 OR 2.8, 95% CI 1.2–6.3; NRSimpaired OR 3.3, 95% CI 1.6–6.8). The scoring system, including TUG, ASA, NRS, gender and type of surgery, showed good accuracy (AUC: 0.81, 95% CI 0.75–0.86). The negative predictive value with a cut-off point >8 was 93.8% and the positive predictive value was 40.3%. Conclusions A substantial number of patients experience major postoperative complications. TUG, ASA and NRS are screening tools predictive of the occurrence of major postoperative complications and, together with gender and type of surgery, compose a good scoring system.